Pathological femoral fracture in a doe secondary to osteomalacia: a veterinary clinical case report - Lim, Eric Teik Chung; Abdullah, Faez Firdaus Jesse; Mohamad Nasir, Nurul Nadiah; Wan Ishak, Wan Mohd Sukri; Abba, Yusuf; Bitrus, Asinamai Athliamai; Peter, Innocent Damudu; Hambali, Idris Umar; Mohd Lila, Mohd Azmi (Nexus Academic Publishers, 2019)
In this veterinary clinical case report highlights a clinical case of pathological femoral fracture in a doe secondary due to osteomalacia. An adult female Katjang goat aged 2 years old was presented to University Veterinary Hospital UPM with the complaint of recumbent and musculoskeletal problem. The doe weight was 18.3 kg with a body condition score of 2 out of 5. The history of the case indicates that the doe was found to fell through the floorboards and the left hindlimb was stucked and later the doe was on sternal recumbency and the most obvious sign was the swollen of the left hindlimb. Physical examination upon palpation revealed that crepitus and bone discontinuity can be felt at the left mid femur with warm and pain upon palpation. Diagnostic workouts of radiography and blood biochemistry were performed in this case. The result of blood biochemistry showed that the doe had hypocalcemia and hypophosphatemia which may indicate the doe suffering from a nutritional deficiency of vitamin D. The radiographic findings revealed bone discontinuity at the left mid femur and overriding of the proximal and distal femoral bone fractures with radiological diagnosis of oblique fracture of the left mid femur. Thinning of bone cortex and the presence of increased radiolucency was observed in bone medulla with radiological diagnosis of osteomalacia. Therefore, this clinical case was diagnosed as the doe suffered from pathological femoral fracture secondary to osteomalacia. The farmer was advised to cull the doe due to the welfare, poor prognosis of the case due to the severity and location of the fracture.